Keterampilan Bertanya dengan Pembelajaran PQ4R (Preview, Question, Read, Reflect, Recite, and Review) - Nurul Mahruzah Yulia; Suttrisno (Jurnal Riset Madrasah Ibtidaiyah, 2022)
Learning in the 21st century emphasizes student activity in the learning process. This activity is not only physically active but also mentally active, especially active for scientific thinking. One indicator of the activity is the high intensity of students in asking questions and the quality of questions asked by students. The research conducted in Class IV MI Subulussalam Pucangsimo, Bandarkedungmulyo District, Jombang Regency, aims to analyze students' questioning skills by learning PQ4R on plant parts. This research was conducted using a descriptive research method with an observation instrument that analyzed students' questions both in quantity and quality. The results showed that students' quantitative questioning skills reached 70%, namely 17 students who were actively asking questions. As for the quality, low cognitive level questions still dominate with a percentage of 88% of all questions asked. Therefore, the questioning skills with PQ4R Learning are classified as good with the achievement of the highest level of asking questions at the high cognitive question level at the analysis stage, there is a need for habituation and improvement of high-level questioning skills so that questions are more weighty to discuss and discuss, at the end students' asking skills will also improve better.